Glutamate-amended chicken manure composting reduces nitrous oxide emissions through promoting ammonium assimilation and complete denitrification - Yanan Luo; Yinfeng Yang; Xiaolin Lu; Wenyu Huang; Yaling Peng; Shangyu Lin; Qunliang Li (Journal of Environmental Chemical Engineering, 2026)

Analysis of the species distribution and drug resistance of pathogenic microorganisms causing diabetic foot infections in Southwest China from 2020 to 2024: a retrospective cross-sectional analysis - Shangyu Zhang; Junchi Chen; Rui Sun; Yu Pan; Yusen Zhuo; Li Tang; Jianhua Zhu; Shuyang Li; Lin Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Zero-valent Fe and MnSO4 collectively stimulate the degradation-related functionalities in the bacterial secretome affecting the efficient degradation of lignocellulose during composting - Xiaolin Lu; Qiqiang Zhang; Shangyu Lin; Rongchun Huang; Yinfeng Yang; Naiguo Mo; Shasha Liang; Guangsheng Qin; Qunliang Li (Chemical Engineering Journal, 2025)

Retearing of type B blind cystic aortic dissection: computational fluid dynamics analysis - Hongbing Chen; Yujing Huang; Tong Su; Qi Wang; Minzhu Zhao; Shangyu Zhang; Ruijiao Lin; Jianbo Li (Physical and Engineering Sciences in Medicine, 2025)

Biochemical and structural characterization of the cyanophage‐encoded phosphate‐binding protein: implications for enhanced phosphate uptake of infected cyanobacteria - Fangxin Zhao; Xingqin Lin; Kun Cai; YongLiang Jiang; Tianchi Ni; Yue Chen; Jianrong Feng; Shangyu Dang; Cong‐Zhao Zhou; Qinglu Zeng (Environmental Microbiology, 2022)
Summary To acquire phosphorus, cyanobacteria use the typical bacterial ABC‐type phosphate transporter, which is composed of a periplasmic high‐affinity phosphate‐binding protein PstS and a channel formed by two transmembrane proteins PstC and PstA. A putative pstS gene was identified in the genomes of cyanophages that infect the unicellular marine cyanobacteria Prochlorococcus and Synechococcus . However, it has not been determined whether the cyanophage PstS protein is functional during infection to enhance the phosphate uptake rate of host cells. Here we showed that the cyanophage P‐SSM2 PstS protein was abundant in the infected Prochlorococcus NATL2A cells and the host phosphate uptake rate was enhanced after infection. This is consistent with our biochemical and structural analyses showing that the phage PstS protein is indeed a high‐affinity phosphate‐binding protein. We further modelled the complex structure of phage PstS with host PstCA and revealed three putative interfaces that may facilitate the formation of a chimeric ABC transporter. Our results provide insights into the molecular mechanism by which cyanophages enhance the phosphate uptake rate of cyanobacteria. Phosphate acquisition by infected bacteria can increase the phosphorus contents of released cellular debris and virus particles, which together constitute a significant proportion of the marine dissolved organic phosphorus pool.